The Influence of Road Distribution in Ambon City on the Availability of Access to Public Cemetery Routes - Ramean, Habisi; Salakory, Melianus; Lasaiba, Mohammad Amin (Universitas Pattimura, 2024)
This research aims to reveal the system and management of the Batu Merah Public Cemetery (TPU) in Ambon City, assess the condition of the road distribution in the Batu Merah TPU, and formulate strategies for managing the Batu Merah TPU in Ambon City. The research uses a qualitative descriptive method. The research variables include the principles of public cemetery arrangement as explained by Hutauruk (2010), involving key components such as: 1) Burial Plots (Space Arrangement, Identification, and Numbering), 2) Vegetation Elements (Gardens, Trees, and Plant Selection), 3) Pedestrian Paths (Accessibility and Lighting). Data collection methods in this study are observation, interviews, and documentation. The population in this research context refers to all objects related to the research problem. The population includes all individual cases and various phenomena within the Kebun Cengkeh TPU area. This includes the TPU management structure, existing graves, and the surrounding community associated with the public cemetery. A well-managed Public Cemetery (TPU) will have a positive impact on the community by fulfilling the need for burial spaces. Conversely, if the TPU is not well-organized and managed, it can have negative impacts such as environmental pollution. In Ambon City, the TPU can no longer accommodate more burials. The Ambon City Government needs to immediately realize the provision of new land and manage the TPU well so that community needs are met and social issues do not arise. The Ambon City Government also needs to establish Regional Regulations on the Arrangement and Management of Public Cemeteries to serve as official guidelines in managing TPUs in the city